Answer:
x = - 6 or x = 8
Explanation:
x(x - 2) = 48 ← distribute parenthesis on left by x
x² - 2x = 48 ( subtract 48 from both sides )
x² - 2x - 48 = 0 ← in standard form
to factor the quadratic, consider the factors of the constant term (- 48) which sum to give the coefficient of the x- term (- 2 )
the factors are 6 and - 8 , since
6 × - 8 = - 48 and 6 - 8 = - 2 , then
x² - 2x - 48 = 0
(x + 6)(x - 8) = 0 ← in factored form
equate each factor to zero and solve for x
x + 6 = 0 ⇒ x = - 6
x - 8 = 0 ⇒ x = 8